Strategi Ayah yang Bekerja dalam Membangun Kedekatan Emosional dengan Anak: Perspektif Bimbingan dan Konseling - Fitri Husaibatul Khairat Hsb (Mataram University, 2026)
This study aims to explore the strategies developed by full-time working fathers in building emotional closeness with their elementary school-aged children (6–12 years) from the perspective of Guidance and Counseling. A qualitative approach with a phenomenological design was employed. Six full-time working fathers participated in this study, selected through purposive sampling until data saturation was reached. Data were collected through semi-structured in-depth interviews, non-participant observation, and documentation. Data analysis followed phenomenological procedures encompassing transcription, identification of significant statements, thematic clustering, and construction of essential experience descriptions. Data trustworthiness was ensured through source and technique triangulation as well as member checking. The findings yielded four major themes: (1) strategies for building emotional closeness through consistent emotional communication and simple daily activities; (2) multidimensional barriers to emotional involvement, including physical and psychological fatigue, patriarchal cultural constructs, and the influence of childhood parenting experiences; (3) fathers' adaptive strategies through boundary management between work and family domains; and (4) the meaning of emotional closeness as a source of psychological need fulfillment and intergenerational value transmission. This study affirms that the quality of fathers' emotional involvement is determined more by responsiveness and consistency of psychological presence than by the quantity of time spent. Implications for Guidance and Counseling services include the development of a family counseling model grounded in a systemic approach that integrates all family members comprehensively.